A Study of Agni, its Impact on Kostha Vaddhata (Constipation) and its Management With “Saghrita Lavanei Yukta Narau Annavagraham Peebet” - Sandh, Krisan Kumar; Sahoo, Manoj Kumar (International Research Journal of Ayurveda & Yoga, 2024)
Background: Kostha vaddhata (constipation) is one of the common problems of human beings on society which is mainly based on the state of Agni. Because the vikrita agni is responsible for creating different types of Ajirna which is the initial or earlier symptom of Grahani Dosha. The aim of the study was to explain the principle of application of Gavya–ghrita mixed with saindhav lavana to treat the Kostha vaddhata. Materials and Methods: Based on the signs and symptoms of Kostha vaddhata (constipation), Saindhava Lavana mixed with Ghrita described in Charaka Samhita was taken for clinical trial. Thirty number of patients, satisfying the inclusion criteria, were taken for the present study and all patients were divided into two equal groups, that is, Group A and Group B. The assessment was made before and after treatment. Results: The better result was obtained when Gavya Ghrita mixed with Saindhava Lavana. Discussion and Conclusion: Finally, it can be said that the formulation, that is, Gavya Ghrita mixed with Saindhava Lavana could be the best tool for the management of Kostha Vaddhata and it also justifies the Siddhanta of Maharshi Charaka. Hence, the research needs further studies with larger samples, and increased duration of medicine could be more informative.